The role of kink boundaries in the deformation and recrystallisation of polycrystalline ice. (July 2020) - Seidemann, Meike; Prior, David J.; Golding, Narayana; Durham, William B.; Lilly, Kat; Vaughan, Matthew J.
Abstract: Kinking is a common process in materials with a strong visco-plastic anisotropy but its impact on the plastic deformation and recrystallisation of crystal aggregates is still poorly constrained. Here, kinking is studied via constant stress experiments on polycrystalline ice under relatively low temperature (240 K) and high differential stress (13.3 MPa and 2.7 MPa, with 50 MPa confining pressure). EBSD data analysis shows that samples comprise large and small grains, interpreted as remnant and recrystallised. Boundary trace analyses and misorientation data of kinked remnant grains reveal that kink boundaries are best characterised with rotation axes within the basal plane of the ice crystal. Inferred slip directions within the basal plane are variable and include <11–20>, <10-10> and intermediate directions. Shorter grain boundaries with rotation axes outside the basal plane surround kink boundaries and indicate that non-basal dislocations or ripplocations play a role in accommodating local kink deformation. More kink boundaries per grain and a larger boundary misorientation are generally found in remnant grains in the high-stress sample. At an aggregate level, kinking as a key facilitator for the dynamic recrystallisation process is represented by many straight grain boundaries with basal rotation axes in the remnant and recrystallised grain population. The statistically preferred slip direction within the basal plane is <21–30>, consistent with coupled slip on two crystallographic a-axes with uneven contributions. Graphical abstract: Image 1 Highlights: Kinking produces bands of recrystallised grains with a reduced grain size. Trace analyses and rotation axes distributions are used to constrain slip systems. Kink boundaries are created by basal slip on two a-axes or ripplocations. The <21–30> slip direction is statistically preferred within the basal plane.